1967
DOI: 10.1002/ar.1091590104
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase activity in the harderian gland of anas domesticus

Abstract: The histochemical localization and quantitative levels of acetylcholinesterase and butyrylcholinesterase have been determined in the Harderian glands of normal ducks and ducks fed with salt to increase their serum sodium concentrations;there was no significant difference between the two groups.Acetylcholinesterase was present at a mean concentration of 68.2 pM/gm/hour (range 65.5 -72.7 pM/gm/hour) in the normal Sniraals and 67.6 pM/gm/hour (range 63.8-76.4pM/gm/hour) in the salt-fed gruup; the enzyme was prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The absence of mitotic activity in the secretory epithelia suggests that holocrine secretion is unlikely (Burns, 1974). Secretion in the fowl Harderian gland (type I gland) is also considered to be merocrine (Wight et al, 1971a), while in the duck (type I1 gland), it is also considered to be merocrine by Fourman and Ballantyne (1967) and by Kiihnel and Beier (1973), though Brobby (1972) thought it to be holocrine in this species. Type I11 glands also appear to be merocrine (Burns, 1975 b) .…”
Section: Secretory Mechanismmentioning
confidence: 91%
See 1 more Smart Citation
“…The absence of mitotic activity in the secretory epithelia suggests that holocrine secretion is unlikely (Burns, 1974). Secretion in the fowl Harderian gland (type I gland) is also considered to be merocrine (Wight et al, 1971a), while in the duck (type I1 gland), it is also considered to be merocrine by Fourman and Ballantyne (1967) and by Kiihnel and Beier (1973), though Brobby (1972) thought it to be holocrine in this species. Type I11 glands also appear to be merocrine (Burns, 1975 b) .…”
Section: Secretory Mechanismmentioning
confidence: 91%
“…Stammer (1964) and Fourman and Ballantyne (1967) demonstrated that acetylcholinesterase (AchE) is present in fibers which are related to blood vessels in the interlobular septa and in connective tissues surrounding some of the collecting ducts Both groups suggested that cholinergic fibers may regulate blood flow thoughout the gland in birds.…”
Section: Innervationsmentioning
confidence: 99%
“…The absence of mitotic activity in the secretory epithelia suggests that holocrine secretion is unlikely. Secretion in the fowl Harderian gland is merocrine and in anatids it is also considered to be merocrine by Fourman and Ballantyne (1967) and by Kiihnel and Beier (1973), though Brobby (1972) thought it was holocrine in the duck. With the advent of the electron microscope the distinction between apocrine and merocrine secretion has become blurred (Bloom and Fawcett 1968), and debris in the tubule lumina of avian Harderian glands may well be part of a merocrine-apocrine form of secretion.…”
mentioning
confidence: 99%